2009
DOI: 10.1016/j.nuclphysb.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

N=4 superconformal n-particle mechanics via superspace

Abstract: We revisit the (untwisted) superfield approach to one-dimensional multi-particle systems with N =4 superconformal invariance. The requirement of a standard (flat) bosonic kinetic energy implies the existence of inertial (super-)coordinates, which is nontrivial beyond three particles. We formulate the corresponding integrability conditions, whose solution directly yields the superpotential, the two prepotentials and the bosonic potential. The structure equations for the two prepotentials, including the WDVV equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…to them). The WDVV equations appear also when constructing N = 4 supersymmetric/superconformal extensions of mechanics on n-dimensional Euclidean space (see [9,10,11,12,13,14] and refs. therein).…”
Section: Introductionmentioning
confidence: 99%
“…to them). The WDVV equations appear also when constructing N = 4 supersymmetric/superconformal extensions of mechanics on n-dimensional Euclidean space (see [9,10,11,12,13,14] and refs. therein).…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that it is just the definition of the metric that can be used to establish the relation between the superfield formalism and the curved WDVV equations. Let us use the idea of [13] and calculate the derivative of this metric:…”
Section: The Modified Metricmentioning
confidence: 99%
“…The choice of OSp(4|2) is the unique one consistent with free kinetic terms for the bosonic fields, as long as one insists on the supercharges (4.30) being linear in fermionic variables [41]. Allowing for supercharge terms cubic in the fermionic operators will constrain their coefficient functions by the so-called WDVV equations [38,39,40,42,43,41]. It will be interesting to develop a superspace variant of this more general situation.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%